Estudos nutricionais das populações rurais da Amazônia. II. Rio Negro - Giugliano, Rodolfo; Shrimpton, Roger; Marinho, Helyde Albuquerque; Giugliano, Loreny Gimenes (Acta Amazonica, 1984)
A nutrition survey was performed on a population inhabiting the banks of the River Negro in the State of, Amazonas, Brazil. Black water rivers such a River Negro have poor mineral. economics and low human population densities. All families having children under six years of age along a two hundred kilometer stretch of niver were included in the survey. Sixty families and 121 children, representing 4.8% of the total, rural population of the municipality, were studied. All children were weighed and measured and Subject to a clinical examination. In 60 children haemoglobin and haematocrit determinations were achieved and in 78 children faecal samples analyzed for parasites. The mothers were weighed, measured, interviewed and in 42 of them haemoglobin and haematocrit determinations were achieved.The hygiene situation of, the population was found to be very primitive , with little or no preocupation in treating river water before drinking and the majority defecating in the forest.The still birth Hate of 80/1000 births, the spontaneous abortions rate of 66.7/ 100 pregnancies and the infant mortality of 93.2/1 000 lives births were all very high.Breast feeding was prolonged with an average weaning age of 16 months and 72% of children being breast fed more than a year. Half of the mothers had introduced οther foods by six months of age, principally a pap made from fermented cassava flour. Some 65% of the children were malnourished according to the criteria. of, Gomez, whilst 70% were found to be stunted and 18% wasted. In the first semester of life only 15.8% of children were stunted but in the second six months 63.6% were stunted.In spite of the prolonged breast feeding 25% of children in the first year of life had diarrhoea at the time of the examination. The major peaks for diarrhoea were in the second semester and the second year of life, when acute malnutritian (wasting) was also found to be most prevalent. Children reported as having had a history of frequent diarrhoea were significantly more chronicaly malnourished (stunted) then children without such antecedents.Almost 85% of children examined had intestinal, parasites, with ascaris, hookworm and trichiuris affecting more than 60%. The most common clinical signs of deficiency for specific nutrients were, those for iron and possibly riboflavin and vitamina A. In 71.2% haemoglobin determinations values were below 11 g% and 74.2% of MCHC were below 30, suggesting iron deficiency anemia to be a serious problem in these children.Mothers were more frequently obese than wasted, suggesting that energy on total food intake was not limiting in the population. Three. quarters of, the mothers had eaten fish in the previous twenty four hours and a half had eaten wild game, principally fresh water turtles. Milk products, cereals and pulses were little, consumied with the staple food being fermented cassava flour. The consumption of fruits was limited to bananas and the use of vegetables limited to that- as condiments.Sixty two percent of mothers had inadequate haemoglobin levels, suggesting iron deficiency anemia to be a problem in spite of their apparently high animal protein, low fibre and low phythate diet.